Navigating the Forest: A Bibliometric Analysis of FSC Certification Research with Implications for Indonesia - Medita Hermawan; Wahyu Hidayat (Forest and Nature, 2026)
Forest Stewardship Council (FSC) certification is one of the most influential voluntary instruments for promoting sustainable forest management worldwide, yet limited bibliometric and structured reviews have systematically examined how scientific interest in this topic has evolved. This study maps the structure, growth, and thematic development of FSC certification research, assesses Indonesia’s position within the global research network, and identifies implications for future studies. A bibliometric analysis was conducted using 752 publications indexed in the Scopus database from 1996 to 2026. Metadata normalization was performed using OpenRefine; quantitative indicators were calculated with Bibliomagika®, and collaboration patterns and keyword networks were visualized using VOSviewer. The dataset comprised contributions from 2,415 authors, with 642 publications generating 17,961 citations, resulting in an h-index of 64 and a g-index of 103. Peer-reviewed journal articles dominated the literature (76.06%), indicating strong academic consolidation. Keyword co-occurrence analysis revealed major research clusters focused on forest management, sustainability, certification, ecosystem services, and deforestation. Collaboration networks analysis showed that North American and European institutions play dominant roles, whereas countries with extensive FSC implementation, such as Indonesia, remain weakly connected to the global research network. One key finding is the limited academic attention to recent governance innovations within the FSC,  notably the Regional Forest Stewardship Standards for Smallholders (RFSS) and the Remedy Framework, despite Indonesia being a key implementation context. This study concludes that FSC certification research has developed into a robust, multidisciplinary field, yet important gaps persist. Addressing these gaps, particularly through empirical studies on new FSC policies in tropical forest regions, represents a significant opportunity for future research. Indonesia holds a unique position and should capitalize on it to contribute empirical evidence on the outcomes of these new FSC policies.